Avestan aiiara- and asniia- (Y. 1,17; 2,17, etc.) - Panaino, Antonio (Indo-Iranian journal, 2017)
The present article deals with the semantics of the stems aiiara- and asniia-, which occur in the framework of a particular liturgical formula (Y. 1,17; 2,17, etc.) together with three other designations of temporal ratu-s: one connected with the “month”, māhiia-, and the other two with the “year”, the first one (yāiriia-) concerning the seasonal periods and festivals (Gāhānbār-s), the second one (sarəδa-) referring to the entirety of the year as a longer time period with its potential multiples. The first two terms, in their turn, express two different notions of the “day” as aiiar-/aiian- or as azan-/asn-. I will argue that aiiara- concerns the day in its complete duration (starting from the dawn as the beginning of the diurnal time), probably including the thirty days of the month (as single days or as a multiple of any day). The second word, asniia-, involves the internal divisions and, then, refers to the different gāh-periods. Finally, I shall demonstrate that this semantic difference is better understood in parallel with the logical and mathematic distinction between “discrete” and “continuous” units.